Moth flies and sand flies (Diptera: Psychodidae) in Cretaceous Burmese amber - Stebner, Frauke; Solórzano Kraemer, Mónica M.; Ibáñez-Bernal, Sergio; Wagner, Rüdiger (PeerJ, 2015)
One new subfamily, four new genera and 10 new species of Psychodidae are described from Burmese amber which significantly increases our knowledge about this group in the Cretaceous. Protopsychodinae n. subfam. probably represents the oldest known ancestor of modern Psychodinae and includes three species within two genera: Datzia setosa gen. et sp. n., Datzia bispina gen. et sp. n., and Mandalayia beumersorum gen. et sp. n. Sycoracinae and Phlebotominae are represented by two genera each in the studied material, Palaeoparasycorax globosus gen. et sp. n., Palaeoparasycorax suppus gen. et sp. n., Parasycorax simplex sp. n., and Phlebotomites aphoe sp. n. and Phlebotomus vetus sp. n., respectively. Bruchomyiinae is represented by Nemopalpus quadrispiculatus sp. n. Furthermore, one genus of an incertae sedis subfamily, Bamara groehni gen. et sp. n., is described. The systematic positions of the new taxa are discussed.
Keywords: Psychodidae; New genera; Cretaceous; Burmese amber; New subfamily; New species